2014
DOI: 10.1007/s00405-014-3341-7
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture in the treatment of tinnitus: a systematic review and meta-analysis

Abstract: This study aimed at a systematic review and meta-analysis of all available randomized controlled trials (RCTs) using acupuncture to treat tinnitus. Five electronic databases, in both English and Chinese, were searched. All studies in our review and meta-analysis included parallel RCTs of tinnitus patients which compared subjects receiving acupuncture (or its other forms, such as electroacupuncture) to subjects receiving no treatment, sham treatment, drugs or basic medical therapy. Data from the articles were v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 16 publications
1
49
0
1
Order By: Relevance
“…Some authors have reported that acupuncture alone (22) or combined with Qi-training (2) could modulate cardiac autonomic functions and reduce tinnitus-related symptoms in patients with chronic tinnitus. However, a meta-analysis has concluded that the beneficial effect of traditional Chinese acupuncture remains inconclusive for patients with tinnitus (23,24). In this study, we found that the F and C subscores, but not the E subscore, were significantly decreased following our triple-combination therapy.…”
Section: Discussionmentioning
confidence: 47%
“…Some authors have reported that acupuncture alone (22) or combined with Qi-training (2) could modulate cardiac autonomic functions and reduce tinnitus-related symptoms in patients with chronic tinnitus. However, a meta-analysis has concluded that the beneficial effect of traditional Chinese acupuncture remains inconclusive for patients with tinnitus (23,24). In this study, we found that the F and C subscores, but not the E subscore, were significantly decreased following our triple-combination therapy.…”
Section: Discussionmentioning
confidence: 47%
“…Some articles used the diagnostic criterion of WHO, and some articles used Chinese diagnostic criterion. Fourthly, in other studies, the most notable finding was that nearly all Chinese studies reported positive results in the acupuncture research (Liu et al, 2016a), and all the studies that were included in this meta-analysis were Chinese trials. That may lead to positive results in the meta-analysis.…”
Section: Acupuncture For Osteoporosis 19mentioning
confidence: 81%
“…Although research support of nonconventional therapies for tinnitus has been limited, there is increasing justification for including them with SBE therapy. In particular, there is growing evidence for the following approaches: (1) psychological and behavioral therapies, such as cognitive-behavioral therapy (CBT) [ 9 11 ]; (2) mind-body therapies, such as biofeedback and meditation, which target autonomic balance and can be effectively coupled with CBT to independently address psychological and physiological variables [ 12 14 ]; and (3) acupuncture [ 15 , 16 ].…”
Section: Complementary Therapiesmentioning
confidence: 99%
“…On the other hand, most of the English studies reported negative results and used distinct acupoints compared to those utilized in the Chinese studies. An analysis of all data together suggested that acupuncture provided some advantages over conventional therapies for tinnitus in terms of subjective benefit but agreed that no definitive conclusions could be made [ 15 ].…”
Section: Complementary Therapiesmentioning
confidence: 99%